Insulin-Like Growth Factor-1 and Insulin-Like Growth Factor Binding Protein-3 - Biomarkers for Skeletal Maturity Assessment in Class II Malocclusion - Arif Yezdani; Kesavaram Padmavathy; Kishore Kumar (Association of Support to Oral Health Research (APESB), 2024)
Objective: To estimate the serum levels of non-radiologic biomarkers, Insulin-like Growth Factor-1 (IGF-1), and Insulin-like Growth Factor Binding Protein-3 (IGFBP-3) to potentially identify the pubertal growth spurt in skeletal Class II malocclusion subjects. Material and Methods: Eighty subjects (M-38, F-42) with skeletal Class II malocclusion in the age range of 11-18 years were recruited for the cross-sectional study. Human serum IGF-1 and IGFBP-3 were quantitatively assessed by enzyme-linked immunosorbent assay, and the cervical stage (CS) was evaluated from a lateral cephalogram. Results: Gender-wise comparison of the mean serum IGF-1 levels revealed that the initial peak was detected at CS2 in both genders, [males (87.87 ng/mL), females (78.49 ng/mL)]. However, there was a cognizable difference in the second peak of the mean serum IGF-1 levels between males (CS5, 68.58 ng/mL) and females (CS4, 74.63 ng/mL). Mean IGFBP-3 serum levels in male subjects were high in CS4 (47.24 ng/mL) with a further spike in CS6 (50.54 ng/mL), and in female subjects, it was found to be highest in CS3 (51.95 ng/mL) and then in CS5 (49.68 ng/mL). Conclusion: Mean IGF-1 levels exhibited both sexes' prepubertal and late pubertal spikes. Mean IGFBP-3 levels revealed a pubertal and a late pubertal spike in both sexes, with an earlier growth trend observed specific to females compared to males.